Circular Agricultural Model Integrated with Health Products and Experiential Tourism: A Case Study of Tam Dao Mushroom Cooperative - Nguyen Thi Van Anh; Hoang Thanh Tung; Mai Thi Dung; Nguyen Thi Huong; Nguyen Quoc Huy; Dinh Nguyen Van Khanh; Truong Thi Tuyet; Nguyen Hoang Bach; Ngo Bao Chau (World, 2026)
Amid accelerating climate change, natural resource depletion, and rising consumer demand for sustainable, health-promoting products, circular agriculture has emerged as a strategic pathway for reconciling agricultural productivity with environmental and social sustainability; however, empirical evidence on how circular production, health-product innovation, and experiential tourism can be jointly evaluated within a single model remains limited. This study aims to propose a multidimensional value assessment framework for circular agriculture through a case study of the Tam Dao Mushroom Cooperative (TDMC) in Phu Tho Province, Vietnam, centered on the cooperative’s Cordyceps militaris-based production system, nanotechnology-enabled health-product processing, most notably the Nano Cordy Milk functional beverage and Science, Technology, Engineering, and Mathematics (STEM)-oriented experiential tourism activities, comprising guided production tours, hands-on cultivation and processing demonstrations, and on-site product tastings offered to school and university groups, domestic and international tourists, and visiting farmers and cooperatives. The research integrates a case study approach with the Fuzzy Analytic Hierarchy Process (Fuzzy-AHP) to determine the priority weights of value dimensions based on the evaluations of seven experts. The findings identify five key dimensions of value generated by the circular agricultural model: economic value, environmental value, social value, educational value, and tourism value. The Fuzzy-AHP results indicate that economic value has the highest priority weight (Best Non-fuzzy Performance, BNP = 0.4050), followed by environmental value (0.2715), social value (0.1307), educational value (0.1313), and tourism value (0.0621). The study demonstrates that the circular agriculture model not only generates economic benefits but also simultaneously creates significant environmental, social, educational, and tourism values. These findings contribute to the theoretical foundation for assessing the multidimensional value of circular agriculture while providing practical references and policy implications for the sustainable development of circular agricultural models.